Bio-char and pyroligneous liquid from oil palm leaf stem - Ani, Farid Nasir (2012)
The biochar is produced from biomass by a process called pyrolysis. The biomass is heated to very high temperatures in the absence of oxygen leading to the formation of carbon residues or charcoal.